Analisis Akomodasi Duta-Guest House Di Daerah Kotabumi - Hernanda, Angga; Hasanuddin, Hasanuddin; Sari, Romida Rifiana; Eviatun, Esti (Jurnal Ilmiah Manajemen Kesatuan, 2022)
Business is never-ending, this business is increasingly growing along with the development of the population and a lifestyle that wants everything to be served quickly. The businesses that we often encounter are in the form of accommodation such as hotels. A hotel is a building that is managed commercially by providing accommodation facilities for the public with service facilities. A hotel is a building with many rooms that is rented out as a place to stay and eat for people who are traveling, or a form of commercially managed investment, provided for everyone to obtain services, lodging, food and drink. Keywords : Business, accommodation, hotels and services